2008
DOI: 10.1097/mbc.0b013e3283009c69
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate improves endothelial function and decreases thrombin-activatable fibrinolysis inhibitor concentration in metabolic syndrome

Abstract: Procoagulant state, inflammation, and endothelial dysfunction have been documented in metabolic syndrome. Endothelial dysfunction is a strong predictor of cardiovascular events. Studies on the association of thrombin-activatable fibrinolysis inhibitor and thrombosis are still controversial, but substantial evidence suggests that increased thrombin-activatable fibrinolysis inhibitor or thrombin-activatable fibrinolysis inhibits or protects against arterial thrombosis. This study aimed to assess concomitantly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…This finding is consistent with other studies that have shown significantly improved FMD response to hyperemia in patients with metabolic syndrome or hypertriglyceridemia following 6–8 weeks of fenofibrate administration [28-30]. A similar effect, partially related to enhanced reduction in LDL-cholesterol and apoB-100 concentrations, has been shown in T2DM patients treated with statins [31].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other studies that have shown significantly improved FMD response to hyperemia in patients with metabolic syndrome or hypertriglyceridemia following 6–8 weeks of fenofibrate administration [28-30]. A similar effect, partially related to enhanced reduction in LDL-cholesterol and apoB-100 concentrations, has been shown in T2DM patients treated with statins [31].…”
Section: Discussionsupporting
confidence: 91%
“…It is not likely the inner endothelial cell layer, even though longstanding fibrate therapy in both dyslipidemic and diabetic patients has been shown to protect it (Kovacs et al, 2005;Otsuki et al, 2005;Kilicarslan et al, 2008). In the present study, experimental removal of the endothelium did not abolish gemfibrozil's vasorelaxant effects.…”
Section: Effects Of Gemfibrozil On K Ne and Avp Induced Contractionssupporting
confidence: 42%
“…A recent study showed that the -1131T>C polymorphism of the apoA5 gene is responsible for the response to fibrate treatment in subjects with the MetS [62]. In addition to their effect on the dyslipidemia, fibrates decrease thrombinactivatable fibrinolysis inhibitor levels and improve endothelial function in the MetS [63]. Fibrate treatment also reduces the production of postprandial inflammatory cytokines and hepatic-synthesized inflammatory proteins (monohydroxy fatty acids, lipopolysaccharide activated monocyte chemotactic protein-1, macrophage inflammatory protein-1alpha and interleukin-1beta) [64,65].…”
Section: Fibratesmentioning
confidence: 96%